Physical exposure during patient transfer and risk of back injury & low-back pain: prospective cohort study - Jonas Vinstrup; Markus D. Jakobsen; Pascal Madeleine; Lars L. Andersen (BMC Musculoskeletal Disorders, 2020)
Abstract Background Work-related musculoskeletal disorders (MSDs) are common among healthcare workers. Because frequent patient transfer has been associated with increased risk of MSDs, we aim to quantify the physical load associated with commonly-used assistive devices and to investigate associations between accumulated physical exposure and risk of MSDs. Methods By applying an exposure matrix based on objective measurements of electromyography and trunk flexion on a large (n = 1285) prospective cohort, intensity of low-back pain (LBP) and odds of back injury at 1-year follow-up were modelled using linear models and logistic regressions, respectively. The cohort was divided into groups according to physical exposure; i.e. low (1st quartile), moderate (2nd and 3rd quartiles) and high (4th quartile) exposure. Results Exposure profiles are provided for 9 groups of assistive devices, with ceiling lifts and intelligent beds eliciting the lowest physical exposure. In the fully-adjusted model, we report differences in LBP intensity at follow-up between the low and moderate exposure groups (p = 0.0085). No difference was found between the moderate and high exposure groups (p = 0.2967). Likewise, we find no associations between physical exposure and odds of back injury at 1-year follow-up, with a prevalence of 11, 13 and 11% for the three groups, respectively. Conclusions Low physical exposure during patient transfer was prospectively associated with lower intensity of LBP. Consistent use of assistive devices associated with low physical exposure, namely ceiling-lifts and intelligent beds, may play a role in reducing the incidence of MSDs among healthcare workers.